The Fibre-Optic System Detecting the Burning Mazout in Power Boilers - W. Wójcik, W.; Kotyra, A.; Duk, M.; Golec, T. (Elektronika ir Elektrotechnika, 2003)
We present a method of detection mazout inside the vortex pulverised coal burner. Since mazout and coal nozzles are placed very close, only the method utilising differences of flame pulsation seems to be the most appropriate. We used information contained within flame pulsation. After converting the appropriate optical signals into electrical form, we utilised wavelet transforms in finding the discriminating features. Ill. 6, bibl. 4 (in English; summaries in Lithuanian, English, Russian).